Bridging Green Human Resource Management and Digital Capability Through Organizational Learning: A Resource-Based View Perspective for Sustainable Organizational Performance - Togar Naibaho; Endang Sulistya Rini (Journal of Innovative and Creativity, 2025)
The integration of environmental sustainability and digital transformation has become a strategic imperative for organizations seeking long-term competitiveness. Yet, many firms struggle to align Green Human Resource Management (GHRM) and Digital HR Capability (DHRC), resulting in fragmented HR practices and inconsistent sustainability outcomes. Grounded in the Resource-Based View (RBV), Dynamic Capability Theory (DCT), and Knowledge-Based View (KBV), this study conceptualizes GHRM and DHRC as complementary strategic resources that enhance Sustainable Organizational Performance (SOP) through the mediating role of Organizational Learning Capability (OLC). Data were obtained from 205 HR managers representing Indonesia’s manufacturing, energy, and service sectors. The analysis employed a hybrid Partial Least Squares Structural Equation Modeling (PLS-SEM) and Artificial Neural Network (ANN) approach. Results reveal that both GHRM and DHRC significantly influence SOP, directly and indirectly via OLC. The ANN model confirms a non-linear predictive accuracy of 89.2%, validating the robustness of the proposed hybrid framework. Theoretically, this study advances RBV by integrating environmental and digital HR capabilities as dual levers for sustainable competitiveness. Methodologically, it contributes to HRM scholarship by bridging predictive and explanatory paradigms within the context of sustainable digital transformation.